In the eyes of the earl - Vayden, Kristin (Vayden, Kristin. Cambridge brotherhood, 2023)
Collin Morgan, Earl of Penderdale, has discovered that someone is committing crimes in his name, leaving him suspended from his work in the war office. Elizabeth Essex is the daughter of a well-respected professor at Cambridge University and longs to be recognized for her own scholarship, which could ruin her family's good name. Morgan tracks his impersonator to Cambridge, leading him to an old friend, Elizabeth's father. The pair is forced into close proximity, with Elizabeth's secret threatened and Morgan's confrontation with his adversaries at a fever pitch.